THE INFLUENCE OF SELF-ESTEEM, ACHIEVEMENT MOTIVATION, AND WORK DISCIPLINE ON TEACHER PERFORMANCE AT AL-AKHYAR I AND II VOCATIONAL HIGH SCHOOLS - Indra Sakti; Octavianti, Dwi Putri (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
ABSTRACTThis study aims to determine the influence of variables of self-esteem, achievement motivation, and work discipline on teacher performance at SMK Al-Akhyar I and II. In this study using descriptive quantitative methods, the sampling technique in this study uses saturated sampling techniques. The saturated sampling technique is a sampling technique when all members of the population are sampled and relatively small. The data analysis methods used in this study are Validity Test, Reliability Test, Partial Significance Hypothesis Test and Simultaneous Significance Test. The results showed that the variable self-esteem affects teacher performance, achievement motivation affects teacher performance and work discipline affects teacher performance. The results of hypothesis testing show that the variables of self-esteem, achievement motivation and work discipline together have a simultaneous effect on teacher performance. Keywords: Self Esteem, Achievement Motivation, Work Discipline, Teacher Performance